TRANSFORMATION OF THE ENGINEERING THINKING OF COMPLEX SYSTEMS DESIGNER - Mygal, G. (Municipal economy of cities. Series: «Economy science», 2024)
The article analyses the professional thinking of designers of the new formation. The study aims to explore the evolution of approaches to designing complex systems and ensuring their viability, as well as to form principles of hybrid thinking on a transdisciplinary basis necessary for viable systems developers of the future.